Evaluation of a workplace intervention to promote commuter cycling: A RE-AIM analysis - Dubuy, Veerle (BioMed Central, 2013)
BACKGROUND: Originating from the interdisciplinary collaboration between public health and the transportation field a workplace intervention to promote commuter cycling, ‘Bike to Work: cyclists are rewarded’, was implemented. The intervention consisted of two cycling contests, an online loyalty program based on earning ‘cycling points’ and the dissemination of information through folders, newsletters, posters and a website. The study purpose was to evaluate the dissemination efforts of the program and to gain insights in whether free participation could persuade small and middle-sized companies to sign up. METHODS: The RE-AIM framework was used to guide the evaluation. Two months after the start of the intervention a questionnaire was send to 4880 employees. At the end of the intervention each company contact person (n = 12) was interviewed to obtain information on adoption, implementation and maintenance. Comparison analyses between employees aware and unaware of the program were conducted using independent-samples t-tests for quantitative data and chi-square tests for qualitative data. Difference in commuter cycling frequency was assessed using an ANOVA test. Non-parametric tests were used for the comparison analyses between the adopting and non-adopting companies. RESULTS: In total seven of the twelve participating companies adopted the program and all adopting companies implemented all intervention components. No significant differences were found in the mean number of employees (p = 0.15) or in the type of business sector (p = 0.92) between adopting and non-adopting companies. Five out of seven companies had the intention to continue the program. At the individual level, a project awareness of 65% was found. Employees aware of the program had a significantly more positive attitude towards cycling and reported significantly more commuter cycling than those unaware of the program (both p < 0.001). Participation was mainly because of health and environmental considerations. CONCLUSIONS: The results of the dissemination study are promising. The adoption and implementation rates indicate that the ‘Bike to Work: cyclists are rewarded’ program seems to be a feasible workplace intervention. At the individual level, a higher score of commuter cycling was found among the employees aware of the program. Nevertheless, more evidence regarding long term effectiveness and sustainability of the intervention is needed.